Tanggung Jawab Pemerintah Daerah dalam Penegakan Hak Atas Lingkungan Bersih di Pangkalpinang dalam Perspektif UUD 1945 - Muhammad Al Ghifari; Muhammad Adjie Ar Rauuf Mikail; Muhammad Ichlas Ramadhan; Andrian Jeremy Marulitua Sigalingging (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines in depth the responsibility of the Pangkalpinang City Government in maintaining environmental cleanliness. Such responsibility is not merely an administrative obligation but a constitutional mandate as stated in the 1945 Constitution of the Republic of Indonesia. Every citizen, including the people of Pangkalpinang, has the right to live in a clean and healthy environment, while the local government is obliged to ensure the fulfillment of this right. This research analyzes the extent to which the local government has carried out its responsibilities through preventive measures (such as formulating regulations and supervising permits) and enforcement actions (including imposing sanctions and restoring the environment). The findings reveal several obstacles, such as limited budget, weak inter-agency coordination, and low public awareness regarding environmental cleanliness. Therefore, although the legal framework is well established, strong commitment, synergy, and continuous efforts from all stakeholders are required to realize a clean and sustainable Pangkalpinang City.